Solve for x -x/17=-0.9

Math
-x17=-0.9
Multiply both sides of the equation by -17.
-17⋅(-x17)=-17⋅-0.9
Simplify both sides of the equation.
Tap for more steps…
Simplify -17⋅(-x17).
Tap for more steps…
Cancel the common factor of 17.
Tap for more steps…
Move the leading negative in -x17 into the numerator.
-17⋅-x17=-17⋅-0.9
Factor 17 out of -17.
17(-1)⋅-x17=-17⋅-0.9
Cancel the common factor.
17⋅-1⋅-x17=-17⋅-0.9
Rewrite the expression.
-1⋅(-x)=-17⋅-0.9
-1⋅(-x)=-17⋅-0.9
Multiply.
Tap for more steps…
Multiply -1 by -1.
1⋅x=-17⋅-0.9
Multiply x by 1.
x=-17⋅-0.9
x=-17⋅-0.9
x=-17⋅-0.9
Multiply -17 by -0.9.
x=15.3
x=15.3
Solve for x -x/17=-0.9

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top